Fenomena Las Gesek (Friction Welding) Dengan Variasi Waktu Gesek Pada Material AISI 1040 Dengan Kuningan - Sugiyarto; Sofwan, Ibnu; Erwanto, Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Friction welding is one of the metal joining methods, by utilizing the heat generated from the physical contact of two metals in the form of friction that occurs continuously on the two metals to produce a welding joint. This research aims to find out what phenomena occur in the connection between AISI 1040 and Brass. The materials used are AISI 1040 solid cylinder with a diameter of 16 mm and brass solid cylinder with a diameter of 16 mm. This research uses experimental method. The friction time used is 6 minutes, 7 minutes, and 8 minutes with a variation of pressing distance of 3 mm, 4 mm, 5 mm with a rotating speed of 1000 rpm. The free heat process of 200 ℃ was carried out on AISI 1040 before the welding process. From the time variation and pressing distance variation that has been carried out in this study, the results obtained from the two materials do not occur. There are several phenomena seen after the welding process such as the occurrence of plastic deformation in brass and the formation of a brass thermoplastic layer attached to the surface of AISI 1040, in the time variation of 6 minutes and 7 minutes the brass thermoplastic attached to AISI 1040 is small and thin, while in the time variation of 8 minutes the brass thermoplastic layer attached to AISI is quite a lot and thick but no connection has occurred. This friction welding method is likely to connect the AISI 1040 material with brass by increasing the friction time performed.